1991
DOI: 10.1259/0007-1285-64-765-808
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric accuracy at low monitor unit settings

Abstract: Dosimetric accuracies at low monitor units are evaluated for linear accelerators from various manufacturers. A large error is observed in the majority of the accelerators. The error can be positive or negative. Although the error can exceed 20% for the first few monitor units, it is usually less than 5% when more than 10 monitor units are delivered. When low doses are required proper precautions should be taken for dosimetric accuracy including the beam energy, beam flatness and dose per monitor unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…Deviations in dose delivery at LMU from the normally calibrated values were reported for photon beams from different linear accelerators [4,23]. An inaccuracy of > 20% in the delivered dose was indicated for electron beams for the initial few MU.…”
Section: Introductionmentioning
confidence: 97%
“…Deviations in dose delivery at LMU from the normally calibrated values were reported for photon beams from different linear accelerators [4,23]. An inaccuracy of > 20% in the delivered dose was indicated for electron beams for the initial few MU.…”
Section: Introductionmentioning
confidence: 97%
“…This problem has been noticed and a number of publications are available [1,2,4,5,10,11,13,17,18,20,22] which analyze the linearity of the dose monitor system of medical electron linear accelerators (linac) down to 1 MU which is the lowest MU setting which can be used at most linacs. The available results show drastic variations: whereas Hansen et al [11] report minor changes of the order of 1-2% of the relative dose at low MU, very recently Ravikumar et al [18] have measured relative doses which are increased by about 20-40% at low MU.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported the dosimetric characteristics of linear accelerator therapy systems at low MU settings [9]- [14]. Das et al reported dose errors higher than 20% for the first few MUs, which stabilize within 5% at MUs exceeding 10 [10]. According to Li et al, SMLC-IMRT affords accurate dose delivery in low MU segments of the recent Varian TrueBeam (Varian Medical Systems Inc., Palo Alto, CA).…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, when step-and-shoot IMRT was implemented with several low monitor units (MUs) per segment at high dose rates, the dosimetric errors were large [9]- [14]. Among researchers who investigated the beam characteristics at low MU settings, Das et al reported a dosimetric error exceeding 20% [10], and Ravikumar et al measured the deviation in dose delivery as 20% -25% (using 6 and 18 MV photon beams at low MU setting) [11]. By determining the uncertainty in the actual dose at low MUs, we can deliver the target dose to within 卤5% for better tumor control [15].…”
Section: Introductionmentioning
confidence: 99%